Octreotide long-acting release in the treatment of autosomal dominant polycystic kidney disease: a meta-analysis - Jin, Mengyan; Shi, Ping; Yu, Yang (Frontiers in Endocrinology, 2026)
ObjectiveTo systematically evaluate the clinical features and effects of octreotide long-acting release in the treatment of autosomal dominant polycystic kidney disease (ADPKD).MethodsDatabases were searched for randomized controlled trials (RCTs) evaluating octreotide long-acting release (LAR) in ADPKD from inception to December 2024. Two reviewers independently screened studies, extracted data, and assessed the risk of bias. Meta-analysis was performed using Stata 16.ResultsA total of six randomized controlled trials were included. Meta-analysis using a fixed-effects model showed no statistically significant difference in glomerular filtration rate (GFR) between the two groups [SMD = -0.020 (-0.250, 0.210), P = 0.864]. Meta-analysis using a random-effects model showed no statistically significant difference in total kidney volume (TKV) between the two groups [SMD= -0.001(-0.376,0.374), P = 0.996]. A fixed-effects model meta-analysis of a fixed effect model showed a statistically significant reduction in cystic kidney volume (CKV) between the two groups [RR = 1.127 (0.996, 1.276), P = 0.058]. Egger’s test and funnel plot analysis indicated no publication bias for GFR, TKV, or CKV. Sensitivity analysis demonstrated that the study results were robust.ConclusionsOctreotide long-acting release has a certain effect on reducing cystic kidney volume in patients with ADPKD but shows no significant effect on GFR or TKV and does not increase the risk of adverse reactions. These findings provide a certain reference for the clinical treatment of ADPKD; however, additional high-quality studies are still needed for further validation.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251242104.